Grading and hemodynamic follow-up study of arteriovenous malformations with transcranial Doppler ultrasonography - (:unkn) unknown (WILEY, 1998)
This study presents and tests the clinical validity of a hemodynamic grading system that depends on noninvasive transcranial Doppler ultrasonographic parameters. The suggested transcranial Doppler-based grading system was compared with the Spetzler-Martin anatomic grading for prognosticative validity and clinical dependability. We concluded the following: (1) The pulsatility index was shown to be a more dependable transcranial Doppler parameter in the clinical evaluation of an arteriovenous malformation because of two reasons: preoperative pulsatility index findings inversely correlated with arteriovenous malformation volume, and the pulsatility index returned to normal values before the mean blood flow velocity did. Therefore, hemodynamic arteriovenous malformation grading can be based on the pulsatility index. (2) A transcranial Doppler-based hemodynamic arteriovenous malformation grading system correlated highly with the Spetzler-Martin grading in predicting postoperative neurologic deficits and adverse radiologic findings. (3) The presented grading system may contribute to the standardization and quantification of the hemodynamic changes during multidisciplinary management of arteriovenous malformations.
Keywords: arteriovenous malformations; grading; hemodynamics; transcranial Doppler ultrasonography; SONOGRAPHY; HEMORRHAGE; STEAL; EMBOLIZATION; ULTRASOUND; BRAIN; AVMS